Near Infrared light-responsive liposomal contrast agent for photoacoustic imaging and drug release applications - Sivasubramanian, Kathyayini (2016)
Photoacoustic imaging has become an emerging tool for theranostic applications. Not only does it help in in vivo, noninvasive imaging of biological structures at depths but it can also be used for drug release and therapeutic applications. We explore near-infrared light-sensitive liposomes coated with gold nanostars (AuNSs) for both imaging and drug release applications using a photoacoustic imaging system. Being amphiphilic, the liposomes lipid bilayer and the aqueous core enable encapsulation of both hydrophobic and hydrophilic drugs. The AuNSs on the surface of the liposomes act as photon absorbers due to their intrinsic surface plasmon resonance. Upon excitation by laser light at specific wavelength, AuNSs facilitate rapid release of the contents encapsulated in the liposomes due to local heating and pressure wave formation (photoacoustic wave). Herein, we describe the design and optimization of the AuNSs-coated liposomes and demonstrate the release of both hydrophobic and hydrophilic model drugs (paclitaxel and calcein, respectively) through laser excitation at near-infrared wavelength. The use of AuNSs-coated liposomes as contrast agents for photoacoustic imaging is also explored with tissue phantom experiments. In comparison to blood, the AuNSs-coated liposomes have better contrast (approximately two times) at 2-cm imaging depth.